The Difference of Ability to Ask, Scientific Attitude, Motivation Before and After Following Contextual Teaching and Learning Model (Journal of Primary Education, 2017)
The learning model used by teachers in the classroom based on the result of the researcher's initial observation is still conventional, the student's inquiring ability is low, the students' scientific attitude is not maximal and the student's motivation is low. Teachers need to use innovative learning models that are suitable and are PAIKEM. The purpose of this study is to know and analyze the ability to ask, scientific attitude, and motivation of students before and after following the model of learning CTL. The research method is quasi experimental quantitative with one group pretest and posttest design technique. Techniques and instruments of data collection is an observation technique with questioning ability observation instrument and psychometric scale measurement of scientific attitude and psychology scale of student motivation. Data analysis technique using non parametric statistical test. The results showed that the ability to ask students before and after follow the model of learning CTL is not experiencing a significant positive difference whereas scientific attitude and student motivation experienced a significant positive difference. This is reinforced by the results of hypothesis test 1 that is not accepted because the value of Î± = 0, 066 above the value of Î± = 5%. In addition, the results of hypothesis 2 and 3 are Î± values below Î± = 5%.